Associations of medicine use and ejection fraction with the coexistence of frailty and sarcopenia in a sample of heart failure outpatients: a cross-sectional study - Valdiviesso, Rui (2023)
BackgroundFrailty and sarcopenia have been extensively studied in heart failure (HF) patients, but their coexistence is unknown. The aim of this work is to describe the coexistence of these conditions in a sample of HF outpatients and its association with the use of medication and left-ventricular ejection fraction.MethodsParticipants in this cross-sectional study were recruited from a HF outpatients' clinic in northern Portugal. Frailty phenotype was assessed according to Fried et al. Sarcopenia was evaluated according to the revised consensus of the European Working Group on Sarcopenia in Older People.ResultsA total of 136 HF outpatients (33.8% women, median age 59 years) integrated this study. Frailty and sarcopenia accounted for 15.4% and 18.4% of the sample, respectively. Coexistence of frailty and sarcopenia was found in 8.1% of the participants, while 17.6% had only one of the conditions. In multivariable analysis (n = 132), increasing age (OR = 1.13;95%CI = 1.06,1.20), being a woman (OR = 65.65;95%CI = 13.50, 319.15), having heart failure with preserved ejection fraction (HFpEF) (OR = 5.61; 95%CI = 1.22, 25.76), and using antidepressants (OR = 11.05; 95%CI = 2.50, 48.82), anticoagulants (OR = 6.11; 95%CI = 1.69, 22.07), furosemide (OR = 3.95; 95%CI = 1.07, 14.55), and acetylsalicylic acid (OR = 5.01; 95%CI = 1.10, 22.90) were associated with increased likelihood of having coexistence of frailty and sarcopenia, while using statins showed the inverse effect (OR = 0.06; 95%CI = 0.01, 0.30).ConclusionsThe relatively low frequency of coexistence of frailty and sarcopenia signifies that each of these two conditions still deserve individual attention from health professionals in their clinical practice and should be screened separately. Being a woman, older age, having HFpEF, using anticoagulants, antidepressants, loop diuretics and acetylsalicylic acid, and not using statins, were associated with having concomitant frailty and sarcopenia. These patients can potentially benefit from interventions that impact their quality of life such as nutritional and mental health interventions and exercise training.